Diseño y construcción de un prototipo de plataforma salvaescaleras para personas con capacidades especiales con movilidad reducida - Rojas Verdezoto, Luis Alberto (2016)
The design and construction of this mechanism, has the purpose of improving the quality of life for people with special abilities that have mobility issues due to the stairs that are usually are located in buildings. The mechanism will be used to transport a wheel chair user straight up the stairs at an angle of 0 ° to 40 °, thus providing a degree of autonomy in their daily lives The criteria for the design is based on what is available locally, considering appropriate materials for purpose, ergonomics, cost and user safety through scientific research and the use of software packages, in order to provide a safe, comfortable system and allow it to function as autonomously and naturally as possible. Keywords: stair lifts, special abilities, rack and pinion